Influence of BiFeO₃ nanoparticle on the properties of YBa₂Cu₃O₇-δ superconductor for possible enhancement of current density - Che Dzul-Kifli, Nur Athirah (2021)
Superconductivity is a phenomenon where the superconductor’s resistance abruptly turns zero ohm as the material meets the superconductor properties. In this work, the bulk superconductor of YBa2Cu3O7-δ (Y-123) added with BiFeO3 (BFO) nanoparticle in different weight percentage (x = 0.0 wt.%, 0.2 wt.%, 1.0 wt.%, 1.5 wt.% and 2.0 wt.%), is synthesized by using thermal treatment method. Further studies were made upon the bulk sample in order to determine the characteristics and properties of the samples. The samples were characterized by using X-Ray Diffraction (XRD), Alternating Current Susceptibility (ACS), Field emission scanning electron microscopy (FESEM) and Energy Dispersive X-ray spectroscopy (EDX). For the first part, the effect of oxygen flow during the sintering process of Y-123 bulk superconductor is studied. This part found that the results obtained for the sample with the oxygen flow are much better than the Y-123 with no oxygen flow. Further study was made regarding the addition of Y-123 (with oxygen flow) with BFO nanoparticle. Based on XRD results, all samples with BFO addition show a Pmmm space group with orthorhombic crystal structure. The weight percentage for x = 1.0 wt.% gives the highest value of Y-123, and the value is decreasing as higher amount of BFO is added. The higher amount of BFO added had degrades the samples' crystallite size, which shows that the addition does not promote the grain growth of Y-123, while the lattice strain increases with higher addition of BFO. As for the ACS, the value of the Tc-onset is enhanced with the addition of BFO nanoparticle, where the x = 1.5 wt.% give the highest Tc value with 91.91 K.The sample with 1.5 wt.% also shows a high value of Tp with the value of89.15 K. In terms of microstructure properties, the FESEM analysis shows thatthe average grain size of the samples is decreases as BFO is introduced. This result is as expected as the crystallite size value mentioned in XRD also shows the same trend. However, the small grain size is expected to fill in the boundary and thus can help in enhancing the grains connectivity. All in all, the addition of BFO nanoparticle in Y-123 does help to improve the superconducting properties mainly for x = 1.5 wt.%.